Stress Response at different Ages of Weaning in Cattle - Odeon, MM; Munilla, ME; Lado, M; Fino, F De; Maidana, S; Vittone, JS; Romera, SA (International Journal of Environment, Agriculture and Biotechnology, 2019)
Weaning is an inherent husbandry practice in cow-calf beef production systems that impose physical, psychological, and nutritional stressors on calves. In order to characterize the main stressors and corresponding stress responses of calves, two weaning schemes were studied. One of conventional weaning (6 month calves) and another of early weaning (1 month calves). Blood samples were analyzed in an hematology analyzer, the plasma was separated and an analysis of total protein and of cortisol levels was carried. Finally, the response to a vaccine was assessed by analyzing antibody response titers. A significant decrease in the number of lymphocytes and increase in the number of granulocytes was observed in the conventionally weaned group leading to an elevated GR:LY ratio. On day one post-weaning, plasmatic proteins showed a significant increase of similar range in both groups. With regard to cortisol levels, there was a strong increase at day one corresponding to a clear stress response in the conventional weaning group, wheras in the group of early weaning animals only a marginal increase which difficult returned to baseline levels could be observed. As to the antibody response to vaccination, early weaning animals did not show a satisfactory response as was observed in calves subjected to conventional weaning. In conclusion, leukocyte subsets, plasmatic proteins, cortisol levels, and immune status were altered after weaning challenge in both studied age groups of calves. Results indicate weaning as a stressor, regardless of age.